Not about the Food: Social Aspect in Restaurant Dining Experience - Purnomo, Agustina Multi; Ratu, Syukur Pulu Hamu (SOSHUM : Jurnal Sosial dan Humaniora, 2023)
Previous research has identified three social aspects that influence the dining experience: local food, foodscape, and the customer's lifestyle. However, little is known about the relationship between these aspects. This study seeks to address that gap by examining how the foodscape of a restaurant, the customer's lifestyle, and the presence of local food shape the dining experience. The study utilized qualitative research methods and conducted a case study on a restaurant located in a weekend tourist area in Bogor Regency. The case study focused on a cafe that received significant media coverage from 2021 to 2023. Through interviews and observations, it was found that the foodscape of a restaurant and the customer's lifestyle are interdependent in shaping the dining experience. The dining experience was seen as both a vacation and a working activity for customers. However, the study found that the foodscape did not have any relationship with the culture of the restaurant location and the type of food. Foodscape only dealt with the restaurant's ambience. This study suggests that further research is needed to reposition foodscape destinations in a locality context. The foodscape restaurant has developed an atmosphere separate from the local cultural context regarding the local food presentation.